The Symbiotic Future: AI Research vs. Traditional Medical Research in the Digital Health Era - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2023)
The landscape of medical discovery is undergoing a profound transformation, driven by the convergence of established scientific rigor and the exponential pow...
Keywords: Drug Discovery; Digital Health; Diagnostics; Artificial Intelligence; Precision Medicine